Aspectos agronômicos em resposta à adubação orgânica e caracterização química de cones de lúpulo (Humulus lupulus) produzido no sul do Brasil - Nava, Karine Guedes (2023)
The evaluation of plants of Humulus lupulus in the field is important to verify their climatic adaptation and productive capacity. The chemical analysis of the flowers allows to determine their chemical and sensory characteristics, which are the main requirements for the attribution of their market value. In the first chapter, the objective was to evaluate agronomic aspects in response to organic fertilizers of hops grown in the municipality of Dois Vizinhos, Southwest of Paraná. For this experiment were used two varieties, Cascade and Chinook, and three organic fertilizers (cattle manure, sheep manure and poultry litter), grown in two consecutive years. The variables analyzed were: number of cones; size of cones (mm); plant height (m); insertion height of the first lateral branch with cone (m); production per plant (g); chlorophyll analysis and; chemical analysis, through the quantification of essential oils (mL 100 g-1)and α and β-acids (% 100 g-1). Based on the edaphoclimatic conditions in which the experimente was conducted, it was concluded that the cultivar Cascade was more productive (greater number and greater fresh biomass of cones per plant) than the cultivar Chinook in both years. The Chinook variety presented higher content of essential oil with poultry litter fertilization in both years. In the multivariate principal componente analysis (PCA), the variables evaluated (field and chemical) allowed to discriminate the correlations, but did not allow to discriminate well the differences between varieties, years and fertilizers. In the second production cycle, both cultivars produced higher levels of alpha and beta-acids. In the second chapter, the objective was to evaluate hop flowers grown in southern Brazil in the 2021 and 2022 harvests. The treatments consisted of hop samples grown in southern Brazil, in a completely random experimental analysis, with three replications. All samples were in their natural form, dehydrated, vacuum packed and stored in ultra-freezer under temperature below 0 and c. The chemical evaluation of hop cones was composed of two variables: total yield of essential oil (mL 100 g-1) which was extracted from the Clevenger apparatus and determination of α and β-acids (% 100 g-1) by liquid chromatography (HPLC). Based on the results discussed, it is observed that for the agricultural cycle of 2020/2021, the varieties of H. lupulus that yielded the most essential oil come from the state of Rio Grande do Sul. The Comet variety presented in both cycles of cultivation the highest yield of essential oil, as well as α-acids in the first cycle. The variety Nuget, presented the highest content of α-acids in the second cycle. The variety Mitelfrueh, presented the highest content of β-acids in the second cycle. In the multivariate principal component analysis (PCA), the factor "year" showed greater contribution than the factor "cultivar" for data variability.